Brand Loyalty Model in Balinese Village as an Art and Cultural Tourism Destination in National Rural Areas, Case Study on Wanagiri Kauh Village, Tabanan - I Made Bayu Wisnawa; Putu Agus Prayogi; I Ketut Sutapa (Institut Pariwisata dan Bisnis Internasional, 2020)
The village is an Indonesian wealth that has the potential to be developed in the tourism sector in realizing prosperity for all Indonesian people. However, there are still many resources in the village that are not well managed. This study aims to: i) identify tourism potential, ii) formulate strategies based on strengths, weaknesses, opportunities and threats, iii) formulate a brand loyalty model in Wanagiri Kauh Tabanan Bali Village in developing tourism as a village in the national rural area, iv) compile a village potential development plan towards rural tourism. The method used is quantitative and qualitative methods. The quantitative method uses Structural Equation Modeling to form a brand loyalty model with antecedents of Brand Image, Brand Awareness, Service Quality, and Customer Satisfaction. The number of samples is 200 tourists who have visited. Meanwhile, the qualitative methods used include SWOT, and in-depth interviews. The results showed that Wanagiri Kauh Village: i) has natural and cultural tourism potential, ii) tourism potential development strategy by presenting uniqueness as the basis for development, iii) brand loyalty model is largely determined by customer satisfaction, brand awareness, service quality and brand image, iv) development planning by managing all resources through the management function by involving the tourism stakeholder Penta helix.